A Systematic Review on Artificial Intelligence Trends in Education - Prajakta S. Shinde,; Pratiksha N.Jawale-patil,; Rajivkumar S. Mente,; Bapu D. Chendage, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This review paper presents the applications of artificial intelligence in education. It includes the study of teaching techniques, evaluation & communication by using AI techniques to enhance learning outcomes. By leveraging data analytics, personalized learning experiences can be developed, catering to the unique needs of each student and fostering a more engaging educational environment. Such as ITS learning platforms and instruction, streamlining administrative duties, and increasing student involvement. And also using AI education to provide learning to Google Classroom, Zoom, Google Meet, textbooks, Unacademy, etc. These advancements are transforming traditional educational methods, enabling personalized learning experiences that cater to individual student needs. Furthermore, AI tools are enhancing collaborative environments, making it easier for educators and students to engage meaningfully, regardless of their physical location.
Keywords: Artificial Intelligence in Education Intelligent Tutoring Systems (ITS); Learning Management System (LMS); Automated Teaching Tools; Human -AT Interaction